Relationship between integrated living skills teachers’ creative characteristics and school creative climate with their critical and creative thinking teaching practices - Vejian, Gajathiswari (2014)
Teachers have a major role to play in fostering creativity in their students by creating good teaching instructions. Teachers‟ own creativity characteristics and the school creative climate that is challenging and supportive also needed for the teachers to come up with their best quality of creative work. It is said that students‟ creative thinking depends upon effective critical and creative thinking teaching practices from their teachers. This study aims to identify the Integrated Living Skills (ILS) teachers‟ critical and creative thinking teaching practices, to identify the ILS teachers‟ creativity characteristics and the school creative climate. In addition, this study also aims to identify the relationship between creativity characteristics and school creative climate with critical and creative thinking teaching practices. The sample for the study comprised 274 ILS teachers from 38 secondary schools in the state of Selangor chosen by random sampling. This study is quantitative survey approach using questionnaires. The Creativity characteristics Questionnaire (CSQ) by Kumar, Kemmler and Holman (1997) was used to measure the ILS teachers‟ creativity characteristics. For school creative climate, the instruments used is School Creativity Climate Questionnaire by Omenyi, Agu and Odimegwu (2009) and The Teacher Checklist for Creative Thinking Instruction by Hamza and Griffith (2006) is used to measure the ILS teachers‟ critical and creative thinking teaching practices. Data was elicited through questionnaires and subjected to a means, standard deviation and Pearson Correlation analysis. The finding shows that ILS teachers often (M=4.00, SD=.44) use critical and creative thinking teaching practices in their classroom. The teachers also somewhat agree (M=3.21, SD=.31) that they use their creativity characteristics to engage in their creative work and the secondary schools often (M=3.44, SD=.33) encourage and motivate the ILS teachers to create creative climate. The finding also indicates that there is a significant low, positive correlation between the ILS teachers‟ creativity characteristics with critical and creative thinking teaching practices [r (274) = 0.324, p<.01]. The Pearson Correlation analysis also shows that there is a significant moderate, positive relationship between the school creative climate with critical and creative thinking teaching practices [ r (274) = 0.528, p<01]. The results of this study supported the importance of the match between teachers‟ creativity characteristics, school creative climate and critical and creative thinking teaching practices. It is suggested to encourage ILS teachers to attend courses or training on how to improve their creativity characteristics and their teaching practices. School administrators also should take some effort in improving school creative climate.